Optimization of biomass and some metabolites productivity of Merismopedia tenuissima and Spirulina (Arthrospira) platensis grown under stress conditions - Khalifa S.H Eldiehy; Mustafa Ahmed Fawzy; Mohammed Rawway; Usama M. Abdul-Raouf (Zanco Journal of Pure and Applied Sciences, 2020)
The attention to using cyanobacteria as a nutrient supplement has increased due to their nutritional value and high bioactive metabolites contents. The reason behind designing such a study is to illustrate and clarify stress conditions effects like nitrogen and phosphorus supplementation and deficiency, salinity stress, and different pH values on the biomass, lipid, protein, amino acid, and carbohydrate productivities of Merismopedia tenuissima and Spirulina (Arthrospira) platensis. The obtained results revealed that an increase in sodium nitrate by 100% caused an improvement in biomass, protein, and amino acid’s productivity of S. platensis and M. tenuissima by 7.02 % and 7.05, 9.2% and 47.5%, 11.8% and19.5, respectively while 100% nitrogen deficiency enhanced lipid productivity of S. platensis and M. tenuissima to 41% and 94%. Moreover, phosphorus limitation led to a reduction in biomass, protein, amino acid, and carbohydrate S. platensis to 24.3%, 21.1%, 43.3%, and 28.1%, respectively. However, phosphorus-free medium showed an increase in lipid productivity of S. platensis and M. tenuissima by 46.8% and 81.8%, respectively. The addition of 0.05 M NaCl concentration to S. platensis medium stimulates the biomass, protein, and carbohydrate productivity by 6%, 7.75%, and 18.1%, respectively, whilst, among all concentration, zero M NaCl (control) resulted in increasing biomass, protein, and amino acids, whilst, high concentration (0.3M) of NaCl enhanced lipid productivity to 125.9% and 153.5% at S. platensis and M. tenuissima, respectively. Applications of high alkalinity (pH 9) increased the productivities of all studied metabolites in S. platensis and reduction of all mention metabolites in M. tenuissima.